2016
DOI: 10.4269/ajtmh.16-0320
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Virus Infection and Diabetes Mellitus: A Double Negative Impact

Abstract: The impact of chikungunya virus (CHIKV) infection on diabetic patients (DPs) has not been described. We aimed to compare clinical features of CHIKV infection in DPs and nondiabetic patients (NDPs), and to evaluate its effects on glycemic control among DPs. We recorded clinical information and, in DPs, glycemic control. Forty-six DPs and 53 NDPs aged ≥ 20 years living in Haiti, with acute CHIKV infection, were studied. Diabetes duration was 7.1 ± 6.1 years. The most common acute CHIKV clinical manifestations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Systematic analysis of studies that described the epidemiological, demographic and clinical features of CHIKV cases and reported the prevalence of a number of chronic diseases in the infectious disease, has identified 11 reports (Arroyo-Avila et al, 2017;Economopoulou et al, 2009;Padmakumar et al, 2010;Jean-Baptiste et al, 2016;Sá deOliveira et al, 2017;Perti et al, 2016;Crosby et al, 2016;Chusri et al, 2014;Couturier et al, 2012;Tandale et al, 2009;Borgherini et al, 2007) with 2,773 patients (Table 1). This limited number of reports is the result of our strict search strategy and selection criteria and our focus only on the studies recording the prevalence of comorbidities in CHIKV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic analysis of studies that described the epidemiological, demographic and clinical features of CHIKV cases and reported the prevalence of a number of chronic diseases in the infectious disease, has identified 11 reports (Arroyo-Avila et al, 2017;Economopoulou et al, 2009;Padmakumar et al, 2010;Jean-Baptiste et al, 2016;Sá deOliveira et al, 2017;Perti et al, 2016;Crosby et al, 2016;Chusri et al, 2014;Couturier et al, 2012;Tandale et al, 2009;Borgherini et al, 2007) with 2,773 patients (Table 1). This limited number of reports is the result of our strict search strategy and selection criteria and our focus only on the studies recording the prevalence of comorbidities in CHIKV.…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles were excluded at the full text review stage as they were either not related to the study objectives (4 studies), not reporting prevalence of chronic disease in CHIKV (3 studies), case reports with small numbers of cases (i.e., <3 cases; 2 reports), or a review article (see Figure 1 and Supplementary Table S1). After identifying one study through bibliography searching, 11 reports were included for systematic review and meta-analysis (Arroyo-Avila et al, 2017;Economopoulou et al, 2009;Padmakumar et al, 2010;Jean-Baptiste et al, 2016;Sá deOliveira et al, 2017;Perti et al, 2016;Crosby et al, 2016;Chusri et al, 2014;Couturier et al, 2012;Tandale et al, 2009;Borgherini et al, 2007).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The exacerbation of underlying chronic comorbid conditions by CHKV has been studied in individuals with diabetes mellitus. The infection may worthen the glycemic control and results in greater morbidity than in individuals without diabetes mellitus . Working from the electronic medical recard of the Veterans Health Administration System, one study reported that overall mortality at the acute stage was low.…”
Section: Current Case Definitionmentioning
confidence: 99%
“…The infection may worthen the glycemic control and results in greater morbidity than in individuals without diabetes mellitus. 33 Working from the electronic medical recard of the Veterans Health Administration System, one study reported that overall mortality at the acute stage was low. However, and similarly to what was described for seasonal influenza infection, 35 the mortality related to CHIKV is also probably delayed to months after the acute phase.…”
Section: Compounding Effects Of Comorbid Chronic Conditionsmentioning
confidence: 99%